Ectopic epipericardial fat necrosis: a case report - Ryusei Yoshino; Masaki Nakatsubo; Nanami Ujiie; Akane Ito; Nana Yoshida; Naoko Aoki; Masahiro Kitada (Surgical Case Reports)
Abstract Background Epipericardial fat necrosis (EFN) is a rare disease in which local inflammation and necrosis occur in the adipose tissue surrounding the heart, particularly epicardial fat. Few cases of EFN in which surgical resection was performed have been reported. We report a case of EFN after surgical resection of a right extrapulmonary tumor, in which a malignant disease could not be excluded. Case presentation A 75-year-old male patient presented with fever and chest pain. A contrast-enhanced computed tomography scan of the chest revealed a lesion, 53 × 48 mm in size, with mixed fatty density spanning the middle and lower lobes of the right lung. Thoracic magnetic resonance imaging (MRI) revealed a mass with mixed fat and soft tissue density in the same area; the lesion was contiguous with pericardial fatty tissue. The tumor was diagnosed as a liposarcoma or teratocarcinoma based on imaging results; however, the possibility of lung cancer could not be excluded. Finally, EFN was diagnosed based on the postoperative histopathological examination. The patient underwent surgical resection of the suspected right extrapulmonary tumor. The intraoperative findings revealed a mediastinal mass contiguous with pericardial fat located between the middle and lower lobes. Intraoperative pathological examination of the lesion was performed using a needle biopsy; however, no definitive diagnosis was made. The tumor may have invaded the middle lobe of the right lung, and partial resection of the right lower lobe was performed in addition to resection of the middle lobe of the right lung. The patient was followed up every 3 months without adjuvant therapy. No recurrence was reported at 1 year after surgery. Conclusion EFN should be considered in the differential diagnosis of an extrapulmonary tumor when continuity with the pericardial space is observed on MRI or other imaging studies. Surgical resection is useful in the diagnosis and treatment of EFNs. Preoperative three-dimensional reconstructive imaging and MRI should be used to identify vascular structures and confirm the continuity of the lesion with the surrounding tissues to ensure safe and rapid tumor removal.